Preparation of 3[(-carboxyphenyl) methylene] -hydrazinecarboxamide for immunoassay of nitrofuran antibiotics - Azmi, Azima (2011)
Currently, analysis of Semicarbazide (SEM) is being carried out using LC-MS/MS instrumentation. It is a need to developed rapid immuno based test kit. We described the synthesis of modified SEM hapten has been carried out through chemical reaction. Polyclonal antibody (pAb) was produced to detect Semicarbazide (SEM), metabolite as a marker residue of nitofurazone in animal food production. A carboxyphenyl derivative of SEM was synthesized following derivatisation of 4-carboxylbenzaldehyde (4-CBA). The modified SEM hapten was characterized using thin layer chromatography (TLC) with Rf value of 0.53 in crystalline form. The fourier transform infra-red (FTIR) spectrum exhibits the peaks at Vmax 3584cm-1 for C=O (carboxylic group). The melting point for the synthesized hapten is 220-223oC. After purification of hapten, the newly developed hapten was then conjugated to keyhole limpet hemocyanin (KLH) as immunogen using 1-ethtyl-3-(dimethylaminopropyl) carbodiimide hydrochloride (EDC) method for conjugation purpose. This immunogen (SEM-KLH) were used to immunize two New Zealand white rabbit to produce polyclonal antibody against newly developed hapten. Using direct enzyme linked immunoassay (ELISA) method, titer determination of the developed antibody of 0.01mg/ml was obtained. For conjugation efficiency electrophoresis gel SDS-PAGE were carried out using 10-7% of resolving gel. This is to identify protein band according to commercial protein marker. No band occur for both of this resolving gel concentration but band for KLH occur at 7% resolving gel but no band for conjugated hapten-protein. Another confirmation of the developed antibody efficiency test is done using surface plasmon resonance which a well is known as biosensor instrument. According to the result, limit of detection for this antibody is up to 0.1 x 10-7 mg/ml compared to ELISA method